All-trans-retinoic acid improves immunocompetence in a murine model of lipopolysaccharide-induced immunosuppression - Martire Greco, Daiana (2014)
Secondary infections due to post-sepsis immunosuppression is a major cause of death in septic patients. Strategies aimed at restoring immune functions offer a new perspective. We used LPS-immunosuppressed (IS) mice to analyze the effects of all-trans Retinoic Acid (ATRA) on different immune parameters. IS mice showed decreased lymphocyte and increased myeloid-derived suppressor cells (MDSC) counts in lymph nodes. They also showed an impaired in vitro T cell proliferation,mediated by MDSC. ATRA administration restored T cell proliferation, associated to a decreased number of live MDSC. IS mice treated with ATRA showed an increased number of CD4+ and CD8+ T cells. ATRA partially improved the primary humoral immune response, even when the immunossuppression was first established, and ATRA administered afterwards. Our results demonstrate that ATRA restores immunocompetence, modulating the number of leukocytes and the survival of MDSC,representing a supplementary potential strategy in the treatment of the immunosuppressive state of sepsis.